Absentee Indians & other poems - Blaeser, Kimberly M. (Native American series (East Lansing, Mich.), 2002)
Absentee Indians and Other Poems evokes personal yet universal experiences of the places that Native Americans call home, their family and national histories, and the emotional forces that help forge Native American identities. These are poems of exile, loss, and the celebration of that which remains. Anchored in the physical landscape, Blaeser's poetry finds the sacred in those ordinary actions that bind a community together. As Blaeser turns to the mysterious passage from sleeping to wakefulness, or from nature to spirit, she reveals not merely the movement from one age or place to another, but the movement from experience to vision.